Fibroma in a Wistar Laboratory Rat – A Case Report - Venkatesn, P.S.; M. Eswarya; S. Sowmiya; M. Madhavaselvi (The Indian Veterinary Journal, 2026)
Laboratory rats can occasionally develop fibromas. This case study reports on a fibroma in an 18-month-old female Wistar rat observed during routine examination at Mass Biotech, Chengalpet, Tamil Nadu. After necropsy, a noticeable subcutaneous abdominal lump was found, showing a well-encapsulated mass the size of a lemon (8 cm in diameter), which was removed. The diagnosis of fibroma was confirmed by histology.